Ketogenic diet in treating sepsis-related acquired weakness: is it friend or foe? - Miao, Yanmei; Xie, Leiyu; Chen, Shaolin; Zhang, Xiaoming; Liu, Wenjie; Xie, Peng (Frontiers in Nutrition, 2024)
Background：Sepsis is the body's extreme response to an infection leading to organ dysfunction. Sepsis-related acquired weakness (SAW), a critical illness closely related to metabolic disorders, is characterized by generalized sepsis-induced skeletal muscle weakness, mainly manifesting as symmetrical atrophy of respiratory and limb muscles. Muscle accounts for 40% of the body's total mass and is one of the major sites of glucose and energy absorption. Diet affects skeletal muscle metabolism, which further impacts physiology and signaling pathways. The ketogenic diet (KD) is a high-fat, low-carbohydrate diet that has shown benefits in patients with a variety of neuromuscular disorders.Patients with SAW are in a hypermetabolic state and can consume approximately 1% of total body muscle mass in a day. Due to the decreased total body energy expenditure secondary to starvation, skeletal muscles enter a low metabolic state, with reduced gluconeogenesis and protein consumption and elevated levels of ketone bodies. The latest research suggests that KD may be a new strategy for SAW prevention and treatment, but its mechanism is still unclear. Objective：Our article aims to explore the effect and mechanism of KD on SAW. And we hope that our review will inspire further 3 research on the KD and foster the exploration of novel strategies for combating SAW. Methods: Search medical databases and related academic websites, using keywords such as " Sepsis-related acquired weakness ", " ketogenic diet ", and "skeletal muscle", and select representative literature. Using the method of induction and summary, analyze the effect and mechanism of KD on SAW. Results: Compared with early nutrition, KD has a more protective effect on SAW, but its mechanism is complex. Firstly, KD can alter energy metabolism substrates to affect SAW's energy metabolism; Secondly, KD can directly act as a signaling molecule to improve mitochondrial function in skeletal muscle and stimulate skeletal muscle regeneration signaling molecules; Thirdly, KD can affect the gut microbiota to exert anti-inflammatory effects, enhance immunity, and thus protect SAW. Conclusions: KD has a protective effect on SAW, which includes improving energy metabolism, stimulating muscle regeneration signals, optimizing gut microbiota composition, and reducing inflammation and oxidative stress.